Criteria, Indicators and Levels of Research of Future Teachers' Readiness for Organization of Dialogic Teaching for Primary School Students - Kateryna Fomin (Vasyl Stefanyk Precarpathian National University, 2020)
The article substantiates the necessity to study the criterion-content and level structure regarding the formation of readiness of future elementary school teachers to organize dialogic teaching. While creating the program of the experimental work the author has taken into account the basic postulations of psychological and pedagogical science, concerning the problem of the readiness of future specialists to organize dialogic teaching, professionalism of activity and communication and dialogic pedagogical communication. The article offers indicative criteria for studying the readiness of future elementary school teachers to organize dialogic teaching of students: need-motivational, cognitive, social-communicative, reflexive-value and operational-activity, as well as indicators of their detection. The levels of readiness of future elementary school teachers to organize dialogic training are determined - high, medium and low. The author presents the results of the empirical study of the state of students' readiness for dialogic teaching of primary school students according to the need-motivational criterion. The results of diagnostics of future teachers' motivation of achievement, understanding of their motivational structure of dialogic teaching, internal motivation of their readiness for self-development, resistance to external influences (in particular, results of ranking by the degree of importance of motives of future pedagogical professional activity) are presented. It is proved that the introduction into the process of training of primary school teachers of the author's model allows to change substantially the motivation of future specialists for future professional activity.